Agreement and repeatability of intraocular pressure measurements between SK-5500B and Icare IC200 tonometers in sitting and supine positions: a comparative study - Li, Nan; Chen, Yucong; Qiu, Kunliang; Guan, Zhiqiang (Frontiers in Physiology, 2026)
IntroductionAccurate intraocular pressure (IOP) measurement is vital in glaucoma management, yet the gold standard (Goldmann applanation tonometry) is limited to seated measurements. Rebound tonometers like the Icare IC200 and the newer SK-5500B offer portability for assessing posture-induced IOP changes, but their measurement consistency requires validation. This study aims to evaluate the agreement and repeatability of IOP measurements between the SK-5500B and Icare IC200 tonometers in sitting and supine positions.MethodsThis prospective study recruited 59 subjects (97 eyes). IOP was measured in both sitting and supine positions by two masked operators using the SK-5500B and Icare IC200 tonometers in a randomized sequence. Subjects were categorized into four groups based on their baseline non-contact tonometry (NCT) readings (<10 mmHg, 10–21 mmHg, 22–30 mmHg, and >30 mmHg). Agreement was assessed using Pearson’s correlation and Bland-Altman analysis. Correlation was evaluated using Pearson’s correlation coefficient (r). Intra- and inter-operator repeatability were determined by within-subject standard deviation (Sw), coefficient of variation (CV), and intraclass correlation coefficient (ICC). The correlation between the device and central corneal thickness (CCT) or axial length (AL) was also analyzed.ResultsThe SK-5500B and Icare IC200 showed a strong positive correlation across all conditions (both positions and both operators) (r ≥ 0.90, P < 0.0001). Bland-Altman analysis demonstrated small mean bias, but the limits of agreement were relatively wide between the two tonometers. Both tonometers exhibited excellent intra-operator (ICC ≥ 0.99) and inter-operator (ICC ≥ 0.99) repeatability. IOP measurements from both tonometers did not show a significant correlation with CCT or AL (P > 0.05).ConclusionDespite wide limits of agreement in Bland-Altman analysis, the SK-5500B showed good agreement and highly comparable repeatability with the Icare IC200 in both sitting and supine positions, supporting its potential as a practical clinical alternative.